A prospective study of intrauterine death cases at a tertiary care hospital - Tai, Nabila N.; Mulchandani, Rinku; Modi, Dipti A.; Rami, Bijal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Intrauterine fetal death is defined as foetus with no signs of life in utero after 20 weeks of gestations. Stillbirth is a useful index to measure the values of antenatal and intra-natal care. Intrauterine fetal death is due to various causes whether it be maternal causes, fetal causes or placental causes. Methods: It was a prospective study, conducted at SSG hospital, Vadodara over a period of 1 year from January 2019 to December 2019. All pregnant women coming to labour room with intrauterine fetal death with gestation age more than 28 weeks were included in study. It included complaints on admission, obstetric profile, mode of delivery, fetal outcomes, placental examination, condition of cord and investigation reports. Results: During the study period of one year, a total of 462 intrauterine fetal deaths were reported amongst 7295 deliveries conducted during the study period. Incidence rate calculated was 63/1000 births. Many of the intrauterine fetal death cases were associated with pregnancy induced hypertension and antepartum hemorrhage. Out of all intrauterine death cases, 410 cases delivered vaginally. Congenital anomalies were also found to be associated with intrauterine death cases. Conclusions: High risk pregnancy cases should be identified during routine antenatal check-ups so that intrauterine fetal death can be prevented. The mode of antepartum and intrapartum surveillance for fetal wellbeing should be advanced to prevent fetal demise.